2022
DOI: 10.1002/advs.202204871
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Transfer Regulates Cell Fate Through Metabolic Remodeling in Osteoporosis

Abstract: Mitochondria are the powerhouse of eukaryotic cells, which regulate cell metabolism and differentiation. Recently, mitochondrial transfer between cells has been shown to direct recipient cell fate. However, it is unclear whether mitochondria can translocate to stem cells and whether this transfer alters stem cell fate. Here, mesenchymal stem cell (MSC) regulation is examined by macrophages in the bone marrow environment. It is found that macrophages promote osteogenic differentiation of MSCs by delivering mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 54 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…Moreover, the osteogenesis process depends on energy metabolism, and energy remodeling in macrophages steers the cell fate of osteoblasts. [51] On the one hand, morphology regulation resulted in competition between Arg2 in the arginine hydrolysis pathway and iNOS in the oxidation pathway. On the other hand, the interconversion between ornithine and citrulline maintained a high level of the citrulline product of the arginine oxidation pathway, inhibiting iNOS expression in turn.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the osteogenesis process depends on energy metabolism, and energy remodeling in macrophages steers the cell fate of osteoblasts. [51] On the one hand, morphology regulation resulted in competition between Arg2 in the arginine hydrolysis pathway and iNOS in the oxidation pathway. On the other hand, the interconversion between ornithine and citrulline maintained a high level of the citrulline product of the arginine oxidation pathway, inhibiting iNOS expression in turn.…”
Section: Discussionmentioning
confidence: 99%
“…Under osteoporotic conditions, Cai et al. found that transferring oxidation-damaged mitochondria from M1-like macrophages to MSCs led to circulating succinate accumulation, increasing ROS levels ( 153 ). This activated hypoxia-inducible factor - alpha (HIF-α), promoted IL-1β expression, and affected MSC osteogenic differentiation.…”
Section: Crosstalk Between Mscs and Macrophages During Sepsismentioning
confidence: 99%
“…Interestingly, MitoEVs can contain both healthy or damaged mitochondria, with different physiopathological consequences on target cells. Recent research has provided solid evidence to support that mitochondria are released from cells for transcellular degradation or transferred to other cells as metabolic support or regulatory messengers [ 36 , 37 , 38 , 39 ].…”
Section: Mitoevsmentioning
confidence: 99%